Randomized double-blind placebo-controlled crossover trial with pyridostigmine in spinal muscular atrophy types 2–4. Issue 1 (9th December 2022) - Stam, Marloes; Wijngaarde, Camiel A; Bartels, Bart; Asselman, Fay-Lynn; Otto, Louise A M; Habets, Laura E; van Eijk, Ruben P A; Middelkoop, Bas M; Goedee, H Stephan; de Groot, Janke F; Roes, Kit C B; Schoenmakers, Marja A G C; et al.
Abstract: Hereditary proximal spinal muscular atrophy causes weakness and increased fatigability of repetitive motor functions. The neuromuscular junction is anatomically and functionally abnormal in patients with spinal muscular atrophy. Pharmacological improvement of neuromuscular transmission may therefore represent a promising additional treatment strategy. We conducted a Phase II, monocentre, placebo-controlled, double-blind, cross-over trial with the acetylcholinesterase inhibitor pyridostigmine in treatment-naïve patients with spinal muscular atrophy types 2–4. We investigated the safety and efficacy of pyridostigmine on fatigability and motor function. Each participant received pyridostigmine and a placebo for 8 weeks, in random order. Primary outcomes were the repeated nine-hole peg test for fatigability and motor function measure. Secondary outcomes were patient-reported effects, endurance shuttle test combined scores and adverse events. We included 35 patients. For the repeated nine-hole peg test, the mean difference was 0.17 s/trial (95% confidence interval: −1.17–1.49; P = 0.8), favouring placebo, and for the motor function measure, 0.74% (95% confidence interval: 0.00–1.49; P = 0.05), favouring pyridostigmine. Around 74% of patients reported medium-to-large beneficial effects of pyridostigmine on fatigability, compared with 29.7% in the placebo arm. This was paralleled by a reduced dropout risk of 70% on the endurance shuttle test combined scores (hazard ratio: 0.30; 95% confidence interval: 0.15–0.58) under pyridostigmine. Adverse events, mostly mild and self-limiting, occurred more frequently under pyridostigmine. No serious adverse events related to the study medication were observed. Patients with spinal muscular atrophy tolerated pyridostigmine well. There were no significant differences in primary outcomes, but the self-reported reduction of fatigability and improved endurance shuttle test combined score performance suggest that pyridostigmine may be useful as an additional therapy to survival motor neuron-augmenting drugs. Trial registration number: EudraCT: 2011–004369-34, NCT02941328 Abstract : Stam et al. report on the placebo-controlled, double-blind, cross-over trial in 35 patients with spinal muscular atrophy types 2–4 to investigate the safety and efficacy of fatigability and motor function of the acetylcholinesterase inhibitor pyridostigmine. Pyridostigmine was well-tolerated, with suggestive evidence of reduced self-reported fatigability and improved performance on endurance tests. Graphical Abstract: Graphical abstract